Cloning and production of fused protein consisting of viral protein 2 from infectious bursal disease virus and hemagglutinin-neuraminidase from Newcastle disease virus - Nor Azlin Alia binti Nor Muhammad (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2015)
Malaysia is exploring opportunities in developing its poultry vaccination programme to produce better poultry vaccine to fight against the two most important diseases of poultry in Malaysia which is Newcastle disease (ND) and infectious bursal disease (IBD) which have been causing constant economic losses to the national livestock industry. Since the commercially available vaccines are consisting of less virulent virus strain that differs from the virulent outbreak strain, the safety and efficacy of the vaccines are becoming great concerns. Development of vaccines consisting of recombinant protein that contains epitopes which able to induce neutralizing antibodies are dominating in the strive for an ideal vaccine, being safe and cheap. Previous studies have shown that the viral surface proteins from Newcastle disease virus (NDV) and infectious bursal disease virus (IBDV) contains epitopes which able to induce neutralizing antibodies against ND and IBD respectively. In this study, viral protein 2 (VP2) from IBDV and hemagglutinin-neuraminidase (HN) from NDV were isolated from IBDV and NDV of local isolates via RT-PCR and cloned into pCR2.1TOPO vector. Subsequently, two constructs of recombinant plasmid containing fused gene was constructed in which full length HN gene from NDV was fused to VP2 of the infectious bursal disease virus (IBDV) while the other construct used partial HN gene. Production of the fused protein was attempted in Pichia pastoris using pPICZαC but was not successful. However, an intact fused protein of VP2-PHN constructed form VP2 and partial HN in pRSETB vector was successfully produced by the Escherichia coli. A protein band with expected molecular weight of 75 kDA was observed in SDS-PAGE and Western blot analysis upon detection with anti-Histidine monoclonal antibody. The VP2-PHN protein produced could be a potential candidate as recombinant subunit vaccine against both IBD and ND upon single immunization.